Hidup Penuh Kasih: Mengamalkan Ajaran Agama untuk Kesejahteraan Bersama - Yustinus J.W. Yuniarto; Nerita Setiyaningtiyas (Publisher STPKat, 2023)
This article aims to carry out a systematic review of the existing literature regarding the model of Catholic religious education with a plural perspective in fostering religious tolerance in Indonesia. This research uses bibliographical tables which consist of several references relevant to the topics discussed. The method used is qualitative research with a literature review design which includes a search strategy, selection of articles based on inclusion and exclusion criteria, finding the main themes, analysis, and synthesis. The findings from this study will provide a comprehensive understanding of the Catholic religious education model with a pluralistic perspective and its role in fostering religious tolerance in Indonesia. The conclusions from this literature analysis will provide recommendations for the development of religious education that is oriented towards the values ​​of religious tolerance